Home Environmental Hazard as Extrinsic Factors For Falls Among Community-Dwelling Elderly (Majalah Kedokteran Bandung, 2025)
Falls among the elderly are a major concern in both clinical practice and public health. Studies have shown that falls occur more frequently at home than outside home.This study aimed to identify the areas and types of home environmental hazards present in the residences elderly individuals. A quantitative descriptive study was conducted from April to May 2024 accross six primary healthcare centers in Bandung, West Java, Indonesia, selected from having the highest number of elderly patients. A total of 100 elderly respondents were recruited using a multistage purposive convenience sampling method. Data collection was carried out using an instrument consisting of two parts: the first part focused on respondent characteristics and the second part on home environmental hazards.The study variables were respondent characteristics and environmental hazards in the terrace, living room, stairs, bedroom, bathroom, kitchen, and garage. Data were analyzed using Microsoft Excel software and presented in tabular form. Results showed that all areas of the home posed potential hazards, with the presence of scattered items on the floor as the commonly identified risk. In specific areas such as the kitchen, high shelves were found, and in the bathroom, there were slippery floors, squat toilets, absence of handrails, and inward-opening bathroom door. Home can be a source of environmental hazards that increase the fall risk among the elderly. It is essential to provide the elderly with adequate information on these risk to encourage preventive actions and, where necessary, home modifications that improve safety and reduce the risk of falls.
Keywords: Elderly; extrinsic factors; fall; home environmental hazards